A comparative study of user acceptance testing between modified waterfall model and extreme programming in small-scale project - Bahrudin, Ida Aryanie (2016)
The successfulness of software development relies on many factors but the selection of software development methodology plays a crucial role in order to complete the project hence to get high quality software. Since the advent of traditional waterfall model, software development methodology is still evolving. There are two categories of software development methodologies that had been implemented recently considered as traditional and Agile methodology. At present, many researchers had conducted comparative studies on different agile software development methodologies. However, literature review had shown few studies investigating the comparison of software development methodologies especially in software testing between traditional methods and Agile modeling. Therefore, this research focused in details on the comparison of user acceptance testing (UAT) in Modified Waterfall model with eXtreme Programming (XP) methodology. The objectives of the research are to perform UAT to the system modules in two case studies, to identify project size and defects in two case studies and to carry out comparative analysis of the error discovery rate from UAT result of Modified Waterfall and XP for selected case studies. A Mann-Whitney U test was performed on XP and Modified Waterfall to compare the difference between error discovery rate means. The analysis shows that there is no significant difference of error discovery rate between both methodologies in the selected case studies. The main contribution of this work is to bring empirical evidence from real life cases that contribute understanding the adoption of both methodologies in small scale project. This study concluded that one of the factor of choosing the software methodology that best fit to the organization is depending on the individual project and circumstances.